Pengembangan LKPD Matematika Materi Sitem Persamaan Linear Dua Variabel (SPLDV) Yang Terintegrasi Pada Nilai- nilai Keislaman - Najla’ Zaul Fadaukas; Widayati Widayati (Pusat Riset dan Inovasi Nasional, 2025)
Lack of contextual-based teaching materials and students' difficulty in understanding the Two-Variable Linear Equation System (SPLDV). This study aims to compile Mathematics LKPD teaching materials for Two-Variable Linear Equation System (SPLDV) Integrated with Islamic Values. This study took place at MTs Al-Ghozaly Wonosobo as the research subjects of mathematics teachers and class VIII-C students of Mts Al-Ghozaly Wonosobo. The pre-research data accumulation technique was carried out by consulting with the mathematics teacher of MTs Al-Ghozaly. Based on the hearing, it was explained that the learning resources applied by the teacher were simple LKS, less innovative in containing material and seemed monotonous, many students had not applied Islamic values ​​in daily activities, the summative test of SPLDV of class VIII-C students was still excessive which was below the KKM. It is hoped that with the existence of this developed LKPD, students are motivated to study and easily understand SPLDV materials that are Integrated with Islamic Values. The development model applied in the study is ADDIE. The data processing technique used validity tests from material and media experts, as well as practicality tests from students using small- and large-class trials. The results of this study were: (1) The average score from material experts was 4.74 and from media experts was 4.8, which are considered highly valid; (2) The percentage of student responses in the small-class trials was 97% and the large-class trials was 88%, which are considered highly practical. Therefore, the Mathematics Student Worksheet (LKPD) on the topic of Systems of Linear Equations in Two Variables (SPLDV) Integrated with Islamic Values ​​is valid and practical.